STUDY ON THE USE OF MODELS IN DECISION SUPPORT BASED COMPUTER - Ire Puspa Wardhani; H. Soetirto Sadikin, Drs., MA. H. Soetirto Sadikin, Drs., MA. (Jurnal Sistem Informasi, 1992)
Computers have brought human civilization into a situation that was never imaginedbefore. world of science, education and business use in earnest the development of anew civilization. management science, an approach in management is more emphasison quantitative analysis of complex, growing rapidly because of the new civilization.therefore, the numbers or the numbers will play a crucial role both in the initialpreparation of the model and the process of completion. completion of a simplemathematical model, it may be done manually, but complicated models, on theconsideration of efficiency and effectiveness, however, also requires completion of acomputer tool to generate sufficient information for subsequent decision making.with the use of computer models of complex quantitative can be resolved quickly sothat the settlement of cases of management science no longer be obstacles andproblems and then switch to model building, data collection, and computer processed.